Reseña bibliográfica : “Why nations fail : the origins of power, prosperity and poverty”, de Daron Acemoglu y James A. Robinson - O'Connor, Ernesto A. (2012)
Fil: O'Connor, Ernesto A. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación "Francisco Valsecchi"; Argentina